Piezoelectric film and preparation method thereof

By adding silica to the polyvinylidene fluoride-barium strontium titanate piezoelectric film and using in-situ polarization treatment method, the problem of low piezoelectric coefficient of the existing film is solved, significantly improving the piezoelectric performance and application range.

CN115101661BActive Publication Date: 2025-04-08CHENGDU XINZHAO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210675970.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-15
Publication Date
2025-04-08
Estimated Expiration
2042-06-15

AI Technical Summary

Technical Problem

The existing polyvinylidene fluoride-strontium barium strontium titanate piezoelectric film has a low piezoelectric coefficient, and the increase in strontium barium titanate will lead to powder agglomeration and material cracking.

Method used

By providing a mixture of vinylidene fluoride and silica, dissolved in a solvent to form a pre-solution, and adding vinylidene fluoride and barium strontium titanate to form a mixed solution, coated on the substrate to form a film to be treated, and in situ polarization treatment is performed to obtain a piezoelectric film.

Benefits of technology

The piezoelectric coefficient of polyvinylidene fluoride-silica-strontium barium titanate piezoelectric film is improved, exceeding 38pc/N, enhancing the piezoelectric properties and application range of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115101661B_ABST
    Figure CN115101661B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of piezoelectric materials, and in particular to a method for preparing a piezoelectric film, which comprises the following steps: providing a mixture of vinylidene fluoride and silicon dioxide in a first predetermined ratio; dissolving the mixture in a solvent to form a pre-solution; providing vinylidene fluoride and barium strontium titanate in a second predetermined ratio, and adding vinylidene fluoride and barium strontium titanate to the pre-solution to form a mixed solution; forming a film to be treated on a substrate with the mixed solution, and obtaining a piezoelectric film after performing an in-situ polarization treatment on the film to be treated. The present invention also provides a piezoelectric film. The piezoelectric film and the preparation method thereof provided by the present invention solve the problem of low piezoelectric coefficient of polyvinylidene fluoride-barium strontium titanate piezoelectric film in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of piezoelectric materials, and in particular to a piezoelectric film and a preparation method thereof. [Background technology]

[0002] Piezoelectric materials are materials that can convert mechanical energy into electrical energy. Among them, piezoelectric polymers, especially polyvinylidene fluoride piezoelectric polymers, have been widely used in sensors, chips, energy engineering, environmental purification, flaw detection, wearable fields, etc. due to their strong piezoelectric properties and unique flexibility. However, the existing piezoelectric film made of a mixture of polyvinylidene fluoride and barium strontium titanate will cause the agglomeration of barium strontium titanate powder and cracking of the material as the amount of barium strontium titanate increases. The piezoelectric coefficient of the material is often low. Therefore, it is of great significance to seek a method to improve the piezoelectric coefficient of polyvinylidene fluoride-barium strontium titanate piezoelectric film. [Summary of the invention]

[0003] In order to solve the problem of low piezoelectric coefficient of polyvinylidene fluoride-barium strontium titanate piezoelectric film in the prior art, the present invention provides a piezoelectric film and a preparation method thereof.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a piezoelectric film, which comprises the following steps:

[0005] providing a mixture of vinylidene fluoride and silicon dioxide in a first predetermined ratio;

[0006] dissolving the mixture in a solvent to form a pre-solution;

[0007] Providing a second predetermined ratio of vinylidene fluoride and barium strontium titanate, and adding the vinylidene fluoride and the barium strontium titanate into the pre-solution to form a mixed solution;

[0008] forming a thin film to be processed by applying the mixed solution on a substrate;

[0009] The piezoelectric film is obtained by subjecting the film to be processed to in-situ polarization treatment.

[0010] Preferably, the mass ratio of vinylidene fluoride to silicon dioxide in the first predetermined ratio ranges from 1 to 10.

[0011] Preferably, the mass ratio of the second predetermined ratio of vinylidene fluoride to barium strontium titanate is in the range of 1-20.

[0012] Preferably, the mass fraction of barium strontium titanate in the mixed solution is 5-20%.

[0013] Preferably, the forming of the mixed solution specifically comprises the following steps: stirring the mixed solution for a first time at a first stirring speed, and then stirring the mixed solution for a second time at a second stirring speed, wherein the second stirring speed is higher than the first stirring speed, and the second time is less than the first time.

[0014] Preferably, forming the thin film to be processed on a substrate with the mixed solution specifically comprises forming a wet film on the substrate by coating, and then drying and annealing to form the thin film to be processed, wherein the thickness of the thin film is 5 micrometers to 50 micrometers.

[0015] Preferably, the drying and annealing treatment specifically comprises the following steps: vacuum drying the wet film to form a dry film, subjecting the dry film to hot air at 70-90° C. to form a dried film, and then annealing at an annealing temperature of 130-180° C. to form a film to be treated.

[0016] In order to solve the above technical problems, the present invention also provides a piezoelectric film, which is prepared by the piezoelectric film preparation method as mentioned above.

[0017] Preferably, the mass fraction of barium strontium titanate in the piezoelectric film is 5-20%.

[0018] Preferably, the piezoelectric coefficient of the piezoelectric film exceeds 38 pc / N.

[0019] Compared with the prior art, the piezoelectric film and the preparation method thereof provided by the present invention have the following beneficial effects:

[0020] 1. An embodiment of the present invention provides a method for preparing a piezoelectric film, which includes the following steps: providing a mixture of vinylidene fluoride and silicon dioxide in a first predetermined ratio; dissolving the mixture in a solvent to form a pre-solution; providing vinylidene fluoride and barium strontium titanate in a second predetermined ratio, and adding vinylidene fluoride and barium strontium titanate to the pre-solution to form a mixed solution; forming the mixed solution on a substrate to form a film to be treated; performing in-situ polarization treatment on the film to be treated to obtain a piezoelectric film. Through the preparation method, a polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film is finally obtained. Based on the above method, a piezoelectric film with a piezoelectric performance of 38pc / N can be obtained, which improves the piezoelectric performance of existing piezoelectric films.

[0021] 2. In the embodiment of the present invention, the mass ratio of the first predetermined ratio of vinylidene fluoride and silicon dioxide is in the range of 1-10; the mass ratio of the second predetermined ratio of vinylidene fluoride and barium strontium titanate is in the range of 1-20; the mass fraction of barium strontium titanate in the mixed solution is 1-20%. The specific limitation of the raw materials improves the piezoelectric properties of the polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film, thereby enabling the polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film to have a wider range of practical applications.

[0022] 3. The mixed solution formed in the embodiment of the present invention specifically includes the following steps: stirring the mixed solution for the first time at a first stirring speed for the first time, and then stirring the mixed solution for the second time at a second stirring speed, wherein the second stirring speed is higher than the first stirring speed and the second time is less than the first time. The mixed solution is stirred for the first time at the first stirring speed, the first stirring speed is 300-400r / min, and the stirring time is 5-6 hours; after the first stirring is completed, the second stirring is stirred for the second time at the second stirring speed, the second stirring speed is 2000-3000r / min, and the stirring time is 30-60 minutes, thereby achieving degassing of the mixed solution.

[0023] 4. The embodiment of the present invention forms a thin film to be treated by applying a mixed solution on a substrate, specifically including forming a wet film on the substrate by coating, and then drying and annealing to form the thin film to be treated. The thickness of the thin film is 5 microns to 50 microns. The uniformity of the wet film is ensured by scraping, making the surface of the wet film smoother. At the same time, scraping can also prevent the appearance of air bubbles in the wet film, further improving the flatness of the piezoelectric thin film, making the thickness and flatness of the piezoelectric thin film better. In addition, the thickness range of the thin film prepared in this embodiment is relatively wide, and the application range of the actual product is relatively wide.

[0024] 5. The drying and annealing treatment of the embodiment of the present invention specifically includes the following steps: vacuum drying the wet film for 5-10 minutes to form a dry film, placing the dry film in a blast oven and drying it with hot air at 70-90°C for 60-90 minutes to form a dried film, and then annealing at an annealing temperature of 130-180°C to form a film to be treated. The vacuum drying takes a short time, does not affect the transparency of the film, and also improves the drying efficiency.

[0025] 6. The embodiment of the present invention further provides a piezoelectric film, which has the same beneficial effects as the piezoelectric film prepared by the above-mentioned piezoelectric film preparation method, so it will not be described in detail here.

[0026] 7. The piezoelectric coefficient of the piezoelectric film of the embodiment of the present invention exceeds 38 pc / N, which is significantly improved compared with the existing vinylidene fluoride film. It has better practical effects and a wider range of applications.

Brief Description of the Drawings

[0027] Figure 1 This is a flow chart of a method for preparing a piezoelectric film provided in the first embodiment of the present invention.

[0028] Figure 2 It is a specific flow chart of forming a mixed solution in a piezoelectric film preparation method provided by the first embodiment of the present invention.

[0029] Figure 3 It is a schematic structural diagram of a thin film polarization device according to the first embodiment of the present invention.

[0030] Figure 4 It is the X-ray diffraction pattern of the piezoelectric film according to the first embodiment of the present invention.

[0031] Figure 5 is a topographical diagram of the piezoelectric film according to the second embodiment of the present invention.

[0032] Description of the accompanying drawings:

[0033] 1. Preparation method; 2. Thin film polarization equipment; 3. Thin film to be processed; 4. Substrate;

[0034] 21. electric field assembly; 22. housing; 23. article carrying platform; 31. first surface; 32. second surface;

[0035] 221. High-voltage electrode terminal; 222. Low-voltage electrode terminal; 231. Rotating tray; 232. Base. [Specific implementation method]

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0037] In the embodiments provided by the present invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined according to A. However, it should also be understood that determining B according to A does not mean determining B only according to A, and B can also be determined according to A and / or other information.

[0038] It should be understood that the "one embodiment" or "an embodiment" mentioned throughout the specification means that the specific features, structures or characteristics related to the embodiment are included in at least one embodiment of the present invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. In addition, these specific features, structures or characteristics can be combined in one or more embodiments in any suitable manner. Those skilled in the art should also be aware that the embodiments described in the specification are all optional embodiments, and the actions and modules involved are not necessarily required by the present invention.

[0039] In various embodiments of the present invention, it should be understood that the size of the serial numbers of the above-mentioned processes does not mean the necessary order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0040] The flow chart and block diagram in the accompanying drawings of the present invention illustrate the possible architecture, function and operation of the system, method and computer program product according to various embodiments of the present application. In this regard, each box in the flow chart or block diagram can represent a module, a program segment or a part of a code, and the module, the program segment or a part of the code contains one or more executable instructions for realizing the specified logical function. It should also be noted that in some alternative implementations, the functions marked in the box can also occur in a sequence different from that marked in the accompanying drawings. For example, two boxes represented in succession can actually be executed substantially in parallel, and they can sometimes be executed in the opposite order, which is determined based on the functions involved. It should be particularly noted that each box in the block diagram and / or flow chart, and the combination of the boxes in the block diagram and / or flow chart can be implemented by a dedicated hardware-based system that performs a specified function or operation, or can be implemented by a combination of dedicated hardware and computer instructions.

[0041] See also Figure 1 The first embodiment of the present invention provides a method 1 for preparing a piezoelectric film, which comprises the following steps:

[0042] Step S1, providing a mixture of vinylidene fluoride and silicon dioxide in a first predetermined ratio;

[0043] Step S2, dissolving the mixture in a solvent to form a pre-solution;

[0044] Step S3, providing a second predetermined ratio of vinylidene fluoride and barium strontium titanate, and adding the vinylidene fluoride and barium strontium titanate into the pre-solution to form a mixed solution;

[0045] Step S4, forming a thin film to be processed on a substrate with the mixed solution;

[0046] Step S5, performing in-situ polarization treatment on the film to be treated to obtain a piezoelectric film.

[0047] It can be understood that through the preparation method 1, a polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film is finally obtained. Silicon dioxide improves the crystallinity of vinylidene fluoride through heterogeneous nucleation. At the same time, silicon dioxide and vinylidene fluoride form a weak intermolecular force, inducing the orientation of the CF bonds in vinylidene fluoride, thereby improving the piezoelectric properties of vinylidene fluoride. Barium strontium titanate improves the crystallinity of vinylidene fluoride through heterogeneous nucleation. At the same time, barium strontium titanate is a nano piezoelectric material. The piezoelectric properties of vinylidene fluoride are improved by controlling the components of barium strontium titanate added to the reactants. Based on the above method, the piezoelectric properties of the vinylidene fluoride piezoelectric film are greatly improved, making the application range of polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film more extensive. In addition, barium strontium titanate easily aggregates with silicon dioxide, causing uneven dispersion. By preparing a pre-solution of vinylidene fluoride-silicon dioxide, adding vinylidene fluoride and barium strontium titanate to the pre-solution, and dissolving silicon dioxide and barium strontium titanate in steps, the problem of barium strontium titanate easily agglomerating with silicon dioxide is solved. At the same time, because the amount of silicon dioxide used is larger than that of barium strontium titanate, adding a large amount of reactants later is likely to cause uneven dispersion. Therefore, this embodiment solves the problem of easy agglomeration of silicon dioxide and barium strontium titanate through a prepolymerization-blending method, and improves the piezoelectric properties of the final product piezoelectric film.

[0048] In the above step S1, the mass ratio of vinylidene fluoride to silicon dioxide in the first predetermined ratio in the mixture is in the range of 1 to 10. Optionally, the mass ratio of vinylidene fluoride to silicon dioxide can also be in the range of 1 to 5, 1 to 1.25, 1 to 8, 1.25 to 7 or 1.25 to 10. Specifically, in the present embodiment, the mass ratio of vinylidene fluoride to silicon dioxide is 1, 1.25, 5, 7, 8 or 10.

[0049] Furthermore, the solvent in the above step S2 includes any one or a combination of chloroform, butanone, N,N-dimethylpyrrolidone, and N,N-dimethylamide. Preferably, when the mixture is dissolved in the solvent to form a pre-solution, the pre-solution is pretreated simultaneously. Specifically, the pre-treatment step is to dissolve the mixture in butanone and ultrasonically clean it using an ultrasonic cleaning device. It can be understood that ultrasonic cleaning causes the insoluble impurities in the pre-solution to precipitate, and after ultrasonic cleaning, the dirt is filtered and separated, thereby achieving the removal of impurities in the pre-solution. Ultrasonic cleaning has a fast cleaning speed and a good cleaning effect.

[0050] Further, in the above step S3, the mass ratio of vinylidene fluoride to barium strontium titanate in the second predetermined ratio ranges from 1 to 20. Optionally, the mass ratio of vinylidene fluoride to barium strontium titanate ranges from 1 to 15, 2 to 15, 4 to 18 or 15 to 20. Specifically, in this embodiment, the mass ratio of vinylidene fluoride to barium strontium titanate is 1, 2, 4, 15, 18 or 20.

[0051] Preferably, the mass fraction of barium strontium titanate in the mixed solution is 5-20%, more preferably 8-18%, and more preferably 10-15%. Specifically, the mass fraction of barium strontium titanate in the mixed solution is 5%, 8%, 10%, 15%, 18% or 20%.

[0052] Please combine Figure 1 and Figure 2 In the above step S3, forming a mixed solution specifically includes the following steps:

[0053] S31, stirring the mixed solution for a first time at a first stirring speed for a first time;

[0054] S32, performing a second stirring at a second stirring speed for a second time.

[0055] Furthermore, in order to make the mixed solution more uniform, the following steps may be included:

[0056] S33, after completing the second stirring, the mixed solution is crushed.

[0057] Specifically, the specific method of stirring is magnetic stirring. In the above step S31, the first stirring speed is 300-400 r / min, and the first time is 5-6 hours. Preferably, the first stirring speed is 400 r / min. After stirring for 5-6 hours at the first stirring speed, barium strontium titanate and vinylidene fluoride are uniformly mixed and distributed in the pre-solution.

[0058] In the above step S32, the second stirring speed is 2000-3000 r / min, and the second time is 30-60 minutes. Preferably, the second stirring speed is 2000 r / min, and after stirring for 30-60 minutes at the second stirring speed, the foam generated by the mixed solution under stirring is removed, and the mixed solution is degassed, so that the piezoelectric material solution is uniform in texture when crystallizing into the piezoelectric material, and there is no cavity caused by bubbles, thereby increasing the piezoelectric coefficient.

[0059] It should be noted that the second time is shorter than the first time. If the second time is too long, more bubbles may be generated, which may cause pore defects on the film surface during the coating of the mixed solution, affecting the piezoelectric properties of the piezoelectric film. The second stirring speed is higher than the first stirring speed. The second stirring speed is used to degas the mixed solution. If the stirring speed is too slow, the speed at which bubbles are generated in the mixed solution will be greater than the speed at which the bubbles are removed. Therefore, the stirring speed needs to be fast so that the bubbles are removed as soon as possible to prevent the bubbles from affecting the piezoelectric properties of the piezoelectric film.

[0060] Specifically, in the above step S33, the crushing step is: using an ultrasonic crushing instrument to treat the mixed solution for 20-30 minutes. It can be understood that the crushing process makes the vinylidene fluoride and silicon dioxide in the mixed solution more uniformly dispersed.

[0061] Optionally, in the above step S4, the mixed solution is formed on a substrate 4 to form a thin film to be treated, specifically including forming a wet film on the substrate 4 by coating, and then drying and annealing to form the thin film to be treated. The substrate 4 includes any one of ITO (indium tin oxide) glass, silicon wafer, copper foil, and aluminum plate. The coating method includes any one of spin coating, spray coating, and full coating. Specifically, the coating method is scraping, and the substrate 4 is a flexible copper foil. Further, the specific steps of coating are to adjust the scale of the scraper to 330μm-400μm; slowly and evenly drip the prepared vinylidene fluoride-silicon dioxide-barium strontium titanate mixed solution on the blade, and after dripping a sufficient amount of the mixed solution, the scraper is scraped at a scraping speed of 10-30mm / s to form a vinylidene fluoride wet film with uniform thickness on the flexible copper foil. It can be understood that the scraping speed can also be 10-25mm / s, 10-20mm / s, 15-25mm / s or 20-25mm / s. Preferably, the scraping speed of the scraper is 20mm / s. By controlling the scraping speed of the scraper, the mixed solution is distributed more evenly on the flexible copper foil. In addition, the prepared mixed solution is slowly and evenly dripped on the blade edge, which ensures the uniformity of the wet film and prevents the appearance of air bubbles in the wet film, thereby improving the flatness of the wet film.

[0062] Furthermore, in the above step S4, the drying process includes the following specific steps: vacuum drying the wet film formed on the flexible copper foil and the flexible copper foil to form a dry film; taking out the dry film and drying it with hot air to form a dried film.

[0063] It can be understood that the temperature of the vacuum drying treatment is 25-35°C, and the time of the vacuum drying treatment is 5-10 minutes. The time required for vacuum drying is short, which will not affect the transparency of the film and also improve the drying efficiency. By setting the temperature of the vacuum drying to 25-35°C, it is avoided that the solvent evaporates quickly due to excessive temperature, causing surface defects of the film. The temperature of hot air drying is 80-95°C, and the drying time is 80-95 minutes. The thickness of the wet film is greater than 200 microns. The thickness of the dried film after the drying treatment is 5-50 microns. The thickness of the film will damage its flexibility, optical properties and curling properties. The film thickness is reduced by the drying step, which not only makes the film lighter but also increases the scope of application of the film.

[0064] Further, in the above step S4, the annealing treatment includes the specific steps of: placing the dried film at an annealing temperature for 45-60 minutes. Optionally, the annealing temperature is 130-180°C. The annealing temperature can also be 130-140°C, 130-160°C, 140-160°C or 140-180°C. Specifically, the annealing temperature is 130°C, 140°C, 160°C or 180°C. It can be understood that by annealing at this annealing temperature, when the annealing temperature is reached, the α crystal form of the vinylidene fluoride in the vinylidene fluoride-silicon dioxide-barium strontium titanate film that does not have piezoelectricity will disappear, and the vinylidene fluoride is in an amorphous state at this time. During the cooling process, the amorphous vinylidene fluoride molecular segments are accelerated to rearrange to generate a β crystal form with piezoelectricity, and, please refer to Figure 4 From the X-ray diffraction pattern, it can be seen that the α crystal completely disappears after annealing, and the β crystal in vinylidene fluoride increases by 10-20% after annealing, that is, the proportion of β crystal in the polymer crystal region and amorphous region increases by 10-20%, further improving the piezoelectric properties of the film, that is, by annealing the film, annealing helps to completely dissipate the α crystal in vinylidene fluoride, and at the same time annealing helps the growth of β crystal.

[0065] See also Figure 3 In the above step S5, the thin film polarization device 2 is performed, which includes a hollow shell 21, an electric field component 22, and an article carrier 23, wherein the electric field component 22 is arranged inside the shell 21. The article carrier 23 includes a rotating tray 231 and a base 232, wherein the shell 21 is arranged on one side of the base 232, and the rotating tray 231 is arranged on the base 232 on the same side as the shell 21 and is accommodated inside the shell 21. Wherein, the film 3 to be processed and the substrate 4 are placed together in the thin film polarization device 2, the rotating tray 231 is used to carry the polarized film 3 to be processed, the film 3 to be processed includes a first surface 31 close to the rotating tray 231 and a second surface 32 away from the rotating tray 231, the base 232 is grounded and makes the potential of the first surface 31 of the film 3 to be processed zero, the electric field component 22 includes a high-voltage electrode end 221 and a low-voltage electrode end 222, the high-voltage electrode end 221 is located on the rotating tray 231, the low-voltage electrode end 222 is located between the high-voltage electrode end 221 and the object carrier 23 to be tested, the potential of the high-voltage electrode end 221 is higher than that of the low-voltage electrode end 222, the ambient gas above the object carrier 23 can be ionized by the high-voltage electrode end 221 and move under the electric field formed by the electric field component 22 and gather on the second surface 32 of the film 3 to be processed, so that an intra-film electric field is formed in the film 3 to be processed along the thickness direction of the film 3 to be processed, so as to polarize the film 3 to be processed.

[0066] Specifically, the in-situ polarization treatment includes the following steps: placing the film 3 to be treated and the substrate 4 together in a polarization device, specifically, the substrate is a flexible copper foil, and the copper foil has a good conductive effect. The side of the substrate 4 away from the film to be treated is connected to the side of the rotating tray away from the base, and the polarization voltage is selected to be 1.5-7.5KV, and the polarization voltage can also be 1.5KV-6KV, 2KV-7KV, 1.5KV-4.5KV or 4.5KV-7.5KV. The polarization voltage can also be specifically 1.5KV, 2KV, 4.5KV, 6KV, 7KV or 7.5KV. The time for polarization treatment is 5-20 minutes. The time for polarization treatment can also be 5-15 minutes, 10-18 minutes, 15-18 minutes, or 15-20 minutes, and the specific time for polarization treatment can also be 5 minutes, 10 minutes, 15 minutes, 18 minutes or 20 minutes.

[0067] It is understandable that conventional polarization methods for treating flexible substrates may cause the substrate to curl and deform, while in-situ polarization is more suitable for treating thinner films, and in-situ polarization can be performed at room temperature, while conventional polarization methods need to be performed at high temperatures. This embodiment greatly shortens the growth time of β-crystals in vinylidene fluoride through in-situ polarization treatment, thereby improving the efficiency of film preparation. Figure 4 From the X-ray diffraction spectrum, it can be seen that the polarization treatment causes the amorphous state in the annealed vinylidene fluoride to continue to orient toward the β crystal, so that the β crystal content in the vinylidene fluoride is increased by another 10-20% on the basis of annealing, that is, the proportion of β crystal in the final piezoelectric film reaches 40-43%, and the increase in the β crystal content further improves the piezoelectric properties of the piezoelectric film. It can be seen that the annealing treatment has limited improvement in the conversion of the amorphous state orientation in vinylidene fluoride to β crystal. This embodiment uses an in-situ polarization method to improve the efficiency of film preparation while further increasing the β crystal content on the basis of annealing. The piezoelectric properties of the film are further improved by in-situ polarization treatment of the film to be treated. In addition, stretching is used to increase the β-crystal content. Stretching will cause uneven surface of the piezoelectric film, thus affecting the piezoelectric properties of the piezoelectric film. At the same time, stretching will destroy the intermolecular force, making it difficult to evenly distribute the β-crystal inside the film, resulting in uneven piezoelectric properties. Therefore, in-situ polarization can improve the piezoelectric properties of the piezoelectric film compared to stretching and conventional polarization methods.

[0068] The thickness of the piezoelectric film of this embodiment is 5 microns to 50 microns. The thickness of the piezoelectric film can also be 5 microns to 20 microns, 10 microns to 40 microns, 20 microns to 30 microns or 20 microns to 50 microns. Specifically, the thickness of the piezoelectric film is 2 microns, 10 microns, 20 microns, 30 microns, 40 microns or 50 microns. The film thickness range prepared by the preparation method 1 of this embodiment is relatively wide, and the application range of the film to actual products is relatively wide.

[0069] The second embodiment of the present invention provides a piezoelectric film, which is prepared based on any of the above-mentioned piezoelectric film preparation methods 1. The mass fraction of barium strontium titanate in the piezoelectric film is 5-20%, and after testing, the piezoelectric coefficient of the piezoelectric film prepared by the present invention exceeds 38pc / N.

[0070] Specifically, the piezoelectric film of this embodiment is prepared by dissolving a mixture of vinylidene fluoride and silicon dioxide in a solvent and pre-treating the mixture to form a pre-solution. Vinylidene fluoride and barium strontium titanate are added to the pre-solution and stirred and degassed to form a mixed solution. The mixed solution is then coated on a substrate 4, and the coated substrate 4 is dried and annealed in turn to form a film to be treated. The film to be treated is further subjected to in-situ polarization treatment to obtain a polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film.

[0071] In this embodiment, in order to better reflect the effect of the amount of components added to the reactants on the response voltage of the vinylidene fluoride piezoelectric film, the present invention further provides the following experimental groups and comparison groups for experimental group 1:

[0072] Experimental Group 1: Provide a mixture of vinylidene fluoride and silicon dioxide; dissolve the mixture in butanone to form a pre-solution. Provide vinylidene fluoride and barium strontium titanate, add vinylidene fluoride and barium strontium titanate to the pre-solution and stir and degas to form a mixed solution. The mass fraction of vinylidene fluoride in the mixed solution is 2.5Wt%, the mass fraction of silicon dioxide is 0.5Wt%, and the mass fraction of barium strontium titanate is 0.2Wt%. The mixed solution is coated on a flexible copper foil, and dried, annealed, and in-situ polarized in sequence to form a film to be tested.

[0073] Experimental Group 2: The difference between Experimental Group 2 and Experimental Group 1 is that the mass fraction of silicon dioxide in the mixed solution is 0.2 wt%, and the mass fraction of barium strontium titanate is 0.1 wt%.

[0074] Experimental Group 3: The difference between the experimental group 1 and the experimental group 3 is that the mass fraction of silicon dioxide in the mixed solution is 0.2 wt%, and the mass fraction of barium strontium titanate is 0.2 wt%.

[0075] Experimental Group 4: The difference between the experimental group 1 and the experimental group 4 is that the mass fraction of silicon dioxide in the mixed solution is 0.5 wt%, and the mass fraction of barium strontium titanate is 0.25 wt%.

[0076] Experimental Group 5: The difference between the experimental group 5 and the experimental group 1 is that the mass fraction of silicon dioxide in the mixed solution is 0.8 wt%, and the mass fraction of barium strontium titanate is 0.3 wt%.

[0077] Experimental Group 6: The difference between the experimental group 6 and the experimental group 1 is that the mass fraction of silicon dioxide in the mixed solution is 0.8 wt%, and the mass fraction of barium strontium titanate is 0.35 wt%.

[0078] Comparative Group 1: The difference between it and the above-mentioned Experimental Group 1 is that the mass fraction of silicon dioxide in the mixed solution is 0 wt%, and the mass fraction of barium strontium titanate is 0 wt%.

[0079] Table 1, Comparison of the response voltage test results of the films obtained in experimental groups 1-6 and comparative group 1

[0080] Experimental group 1 Response voltage(V) Experimental Group 1 11.7 Experimental Group 2 7.7 Experimental Group 3 11.5 Experimental Group 4 9.5 Experimental Group 5 7.2 Experimental Group 6 4.8 Comparison group 1 4.1

[0081] Based on the contents in Table 1, by comparing experimental group 1 and comparison group 1, it can be seen that the addition of silicon dioxide and barium strontium titanate significantly improves the piezoelectric response of the piezoelectric film. The silicon dioxide added in this embodiment improves the crystallinity of vinylidene fluoride through heterogeneous nucleation, and at the same time, silicon dioxide and vinylidene fluoride form a weak intermolecular force, inducing the orientation of the CF bond in vinylidene fluoride, thereby improving the piezoelectric properties of vinylidene fluoride. In this embodiment, barium strontium titanate is added to improve the crystallinity of vinylidene fluoride through heterogeneous nucleation, and at the same time, barium strontium titanate is a nano-piezoelectric material, and the piezoelectric properties of vinylidene fluoride are improved by controlling the components of barium strontium titanate added to the reactants. Through experimental groups 1-6 in Table 1, it can be seen that the mass fraction of silicon dioxide and barium strontium titanate added has a greater effect on the piezoelectric response of the piezoelectric film. When the carbon dioxide or barium strontium titanate components are low, or high, the piezoelectric properties of the piezoelectric film will be reduced. The preparation method 1 of the piezoelectric film in this embodiment innovatively proposes to add silicon dioxide and barium strontium titanate to vinylidene fluoride, and at the same time, through experimental research, the influence of the content of different components of the reactants on the piezoelectric properties of the piezoelectric film is studied, which has a significant effect on improving the piezoelectric properties of vinylidene fluoride.

[0082] In this embodiment, in order to better reflect the superiority of the piezoelectric film prepared by the above-mentioned piezoelectric film preparation method 1 in improving the piezoelectric coefficient, the present invention further provides the following experimental group and comparison group for experimental group 2:

[0083] Experimental group 7: providing a mixture of vinylidene fluoride and silicon dioxide; and dissolving the mixture in butanone to form a pre-solution, wherein the mass ratio of vinylidene fluoride to silicon dioxide is 10.

[0084] Provide vinylidene fluoride and barium strontium titanate, and add vinylidene fluoride and barium strontium titanate to the pre-solution; stir the mixed solution for the first time at a first stirring speed of 400r / min, and the first stirring time is 6 hours. After the first stirring is completed, stir for the second time at a second stirring speed of 200r / min, and the second stirring time is 1 hour. After the second stirring is completed, the mixed solution is crushed for 30 minutes to finally form a mixed solution. Among them, the mass ratio of vinylidene fluoride to barium strontium titanate is 4.

[0085] The mixed solution is coated on the flexible copper foil, and the wet film formed on the flexible copper foil and the flexible copper foil are subjected to vacuum drying to form a dry film; the dry film is taken out and hot air dried to form a dried film. The vacuum drying temperature is 30°C and the time is 6 minutes. The hot air drying temperature is 70-90°C and the hot air drying time is 90 minutes.

[0086] The dried film is placed at an annealing temperature of 140° C. for 45 minutes to form a film to be treated.

[0087] The piezoelectric film was obtained by polarizing the film to be treated, wherein the polarization voltage was 4.5 KV, the polarization time was 15 minutes, and the thickness of the formed piezoelectric film was 10 microns.

[0088] Experimental Group 8: The difference between Experimental Group 8 and Experimental Group 1 is that the mass ratio of vinylidene fluoride to silicon dioxide is 1.25.

[0089] Experimental Group 9: The difference between Experimental Group 9 and Experimental Group 1 is that the mass ratio of vinylidene fluoride to silicon dioxide is 5.

[0090] Experimental group 10: The difference between the experimental group 1 and the experimental group 1 is that the mass ratio of vinylidene fluoride to silicon dioxide is 1:1.

[0091] Experimental group 11: The difference between the experimental group 1 and the experimental group 1 is that the mass ratio of vinylidene fluoride to silicon dioxide is 15.

[0092] Experimental Group 12: The difference between Experimental Group 1 and Experimental Group 1 is that the mass ratio of vinylidene fluoride to barium strontium titanate is 2.

[0093] Experimental Group 13: The difference between Experimental Group 1 and Experimental Group 1 is that the mass ratio of vinylidene fluoride to barium strontium titanate is 3.

[0094] Experimental Group 14: The difference between Experimental Group 1 and Experimental Group 1 is that the mass ratio of vinylidene fluoride to barium strontium titanate is 15.

[0095] Experimental Group 15: The difference between Experimental Group 1 and Experimental Group 1 is that the mass ratio of vinylidene fluoride to barium strontium titanate is 20.

[0096] Experimental Group 16: The difference between Experimental Group 1 and the above Experimental Group 1 is that the first stirring speed is 300 r / min.

[0097] Experimental Group 17: The difference between Experimental Group 1 and the above Experimental Group 1 is that the second stirring speed is 300 r / min.

[0098] Experimental Group 18: The difference between Experimental Group 18 and the above Experimental Group 1 is that the substrate 4 is a silicon wafer.

[0099] Experimental Group 19: The difference between it and the above experimental group 1 is that the scraping speed is 10mm / s

[0100] Experimental Group 20: The difference between Experimental Group 20 and Experimental Group 1 is that the drying process is natural drying at room temperature and pressure.

[0101] Experimental Group 21: The difference between Experimental Group 21 and Experimental Group 1 is that the film to be treated is polarized for 5 minutes using a voltage of 3 KV to obtain a piezoelectric film.

[0102] Experimental Group 22: The difference between Experimental Group 22 and Experimental Group 1 is that the film to be treated is polarized for 5 minutes using a voltage of 20 KV to obtain a piezoelectric film.

[0103] Experimental Group 23: The difference between Experimental Group 23 and Experimental Group 1 is that the thickness of the piezoelectric film is 15 microns.

[0104] Experimental Group 24: The difference between Experimental Group 24 and Experimental Group 1 is that the thickness of the piezoelectric film is 20 microns.

[0105] Comparative Group 2: Vinylidene fluoride and barium strontium titanate were added to butanone in a mass ratio of 10:1 to obtain a mixed solution. The mixed solution was further stirred at a stirring speed of 400 r / min for 8 hours. The mixed solution was coated on a flexible copper foil, dried at room temperature and annealed to obtain a piezoelectric film sample.

[0106] Comparative Group 3: The difference between it and the above-mentioned Experimental Group 1 is that the film to be treated after drying is directly subjected to polarization treatment without annealing treatment.

[0107] Comparative Group 4: The difference between it and the above-mentioned Experimental Group 1 is that the film after annealing treatment is directly used as the film to be tested without the need for polarization treatment.

[0108] Comparative Group 5: The difference between it and the above-mentioned Experimental Group 1 is that: the polarization treatment of the thin film to be treated is specifically: polarizing the thin film to be treated at a voltage of 10 KV for 30 minutes, and other specific steps remain unchanged.

[0109] Comparative Group 6: The difference between it and the above-mentioned Experimental Group 1 is that: the polarization treatment of the thin film to be treated is specifically: the thin film to be treated is polarized at a voltage of 30 KV for 8 minutes, and other specific steps remain unchanged.

[0110] Comparative Group 7: The difference between it and the above-mentioned Experimental Group 1 is that the thickness of the piezoelectric film is 80 microns.

[0111] Table 2, Comparison of the piezoelectric coefficient test results of the films obtained from the experimental groups 7-24 and the comparative groups 5-7

[0112]

[0113] Based on the contents in Table 2, it can be seen from the experimental data of the above experimental groups 7-24 and the comparative groups 2-7 that the piezoelectric film provided by the present invention, compared with the piezoelectric film made of vinylidene fluoride alone or vinylidene fluoride-barium strontium titanate as raw materials, the silicon dioxide and barium strontium titanate added by the present invention improve the crystallinity of vinylidene fluoride through heterogeneous nucleation, so that the piezoelectric coefficient of the piezoelectric film exceeds 38pc / N, specifically in the range of 38pc / N-42pc / N, so that the piezoelectric coefficient is greatly improved.

[0114] Compared with the prior art, the piezoelectric film and the preparation method thereof provided by the present invention have the following beneficial effects:

[0115] 1. An embodiment of the present invention provides a method for preparing a piezoelectric film, which includes the following steps: providing a mixture of vinylidene fluoride and silicon dioxide in a first predetermined ratio; dissolving the mixture in a solvent to form a pre-solution; providing vinylidene fluoride and barium strontium titanate in a second predetermined ratio, and adding vinylidene fluoride and barium strontium titanate to the pre-solution to form a mixed solution; forming a film to be treated on a substrate with the mixed solution, and performing in-situ polarization treatment on the film to be treated to obtain a piezoelectric film. Through the preparation method, a polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film is finally obtained. Based on the above method, a piezoelectric film with a piezoelectric performance of 38pc / N can be obtained, which improves the piezoelectric performance of existing piezoelectric films.

[0116] 2. In the embodiment of the present invention, the mass ratio of the first predetermined ratio of vinylidene fluoride and silicon dioxide is in the range of 1-10; the mass ratio of the second predetermined ratio of vinylidene fluoride and barium strontium titanate is in the range of 1-20; the mass fraction of barium strontium titanate in the mixed solution is 1-20%. The specific limitation of the raw materials improves the piezoelectric properties of the polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film, thereby enabling the polyvinylidene fluoride-silicon dioxide-barium strontium titanate piezoelectric film to have a wider range of practical applications.

[0117] 3. The mixed solution formed in the embodiment of the present invention specifically includes the following steps: stirring the mixed solution for the first time at a first stirring speed for the first time, and then stirring the mixed solution for the second time at a second stirring speed, wherein the second stirring speed is higher than the first stirring speed and the second time is less than the first time. The mixed solution is stirred for the first time at the first stirring speed, the first stirring speed is 300-400r / min, and the stirring time is 5-6 hours; after the first stirring is completed, the second stirring is stirred for the second time at the second stirring speed, the second stirring speed is 2000-3000r / min, and the stirring time is 30-60 minutes, thereby achieving degassing of the mixed solution.

[0118] 4. The embodiment of the present invention forms a thin film to be treated by applying a mixed solution on a substrate, specifically including forming a wet film on the substrate by coating, and then drying and annealing to form the thin film to be treated. The thickness of the thin film is 5 microns to 50 microns. The uniformity of the wet film is ensured by scraping, making the surface of the wet film smoother. At the same time, scraping can also prevent the appearance of air bubbles in the wet film, further improving the flatness of the piezoelectric thin film, making the thickness and flatness of the piezoelectric thin film better. In addition, the thickness range of the thin film prepared in this embodiment is relatively wide, and the application range of the actual product is relatively wide.

[0119] 5. The drying and annealing treatment of the embodiment of the present invention specifically includes the following steps: vacuum drying the wet film for 5-10 minutes to form a dry film, placing the dry film in a blast oven and drying it with hot air at 70-90°C for 60-90 minutes to form a dried film, and then annealing at an annealing temperature of 130-180°C to form a film to be treated. The vacuum drying takes a short time, does not affect the transparency of the film, and also improves the drying efficiency.

[0120] 6. The embodiment of the present invention further provides a piezoelectric film, which has the same beneficial effects as the piezoelectric film prepared by the above-mentioned piezoelectric film preparation method, so it will not be described in detail here.

[0121] 7. The piezoelectric coefficient of the piezoelectric film of the embodiment of the present invention exceeds 38 pc / N, which is significantly improved compared with the existing vinylidene fluoride film. It has better practical effects and a wider range of applications.

[0122] The above is a detailed introduction to a piezoelectric film and a preparation method thereof disclosed in an embodiment of the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technical personnel in this field, according to the idea of ​​the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a piezoelectric film, characterized in that: It includes the following steps: providing a mixture of vinylidene fluoride and silicon dioxide in a first predetermined ratio; dissolving the mixture in a solvent to form a pre-solution; Providing a second predetermined ratio of vinylidene fluoride and barium strontium titanate, and adding the vinylidene fluoride and the barium strontium titanate into the pre-solution to form a mixed solution; forming a thin film to be processed by applying the mixed solution on a substrate; The piezoelectric film is obtained by subjecting the film to be processed to in-situ polarization treatment.

2. The method for preparing a piezoelectric film according to claim 1, wherein: The mass ratio of vinylidene fluoride to silicon dioxide in the first predetermined ratio ranges from 1 to 10.

3. The method for preparing a piezoelectric film according to claim 1, wherein: The mass ratio of vinyl fluoride to barium strontium titanate in the second predetermined ratio ranges from 1 to 20.

4. The method for preparing a piezoelectric film according to claim 1, wherein: The mass fraction of barium strontium titanate in the mixed solution is 5-20%.

5. The method for preparing a piezoelectric film according to claim 1, wherein: The forming of the mixed solution specifically includes the following steps: stirring the mixed solution for a first time at a first stirring speed and for a first time, and then stirring the mixed solution for a second time at a second stirring speed and for a second time, wherein the second stirring speed is higher than the first stirring speed and the second time is shorter than the first time.

6. The method for preparing a piezoelectric film according to claim 1, wherein: The step of applying the mixed solution to form a thin film to be processed on a substrate specifically includes forming a wet film on the substrate by coating, and then drying and annealing to form the thin film to be processed, wherein the thickness of the thin film is 5 micrometers to 50 micrometers.

7. The method for preparing a piezoelectric film according to claim 6, wherein: The drying and annealing treatment specifically includes the following steps: vacuum drying the wet film to form a dry film, blowing hot air at 70-90° C. on the dry film to form a dried film, and then annealing at an annealing temperature of 130-180° C. to form a film to be treated.

8. A piezoelectric film prepared by the piezoelectric film preparation method according to any one of claims 1 to 7.

9. The piezoelectric film according to claim 8, wherein: The mass fraction of barium strontium titanate in the piezoelectric film is 5-20%.

10. The method for preparing a piezoelectric film according to claim 8, wherein: The piezoelectric coefficient of the piezoelectric film exceeds 38 pc / N.

Citation Information

Patent Citations

  • Preparation method of aerogel / PZT nano-powder piezoelectric composite material

    CN112216788A

  • Switch having self-generation type light emitting function

    KR101494437B1